Construction and demolition waste applied to road pavement layers: a systematic review (Research, Society and Development, 2022)
The road pavement is the structure executed on the subgrade whose technical purpose is to resist the efforts and distribute them to the constituent layers, providing safety and comfort to users. The large and growing production of construction and demolition waste in the area of civil construction arouses the interest of cities and companies in using recycled aggregates in paving, since these materials are mostly sold at lower prices than conventional aggregates. Thus, the present work seeks to present a systematic review to evaluate which researches on the application of construction and demolition waste (CDW) were developed between the years 2015 and 2019 and simultaneously analyze in which layer of the road pavement the greatest use occurred. of construction and demolition waste, thus enabling the development of new studies on the subject. It was found that the vast majority of the works evaluated in full developed research by inserting construction and demolition waste into asphalt mixtures, that is, compositions intended for the execution of coating layers.